2017
DOI: 10.1257/aer.20121266
|View full text |Cite
|
Sign up to set email alerts
|

WTO Accession and Performance of Chinese Manufacturing Firms

Abstract: We examine the effects of trade liberalization in China on the evolution of markups and productivity of manufacturing firms. Although these dimensions of performance cannot be separately identified when firm output is measured by revenue, detailed price deflators make it possible to estimate the average effect of tariff reductions on both. Several novel findings emerge. First, cuts in output tariffs reduce markups, but raise productivity. Second, pro-competitive effects are most important among incumbents, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
376
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(436 citation statements)
references
References 58 publications
28
376
1
2
Order By: Relevance
“…Our estimates suggest that, on average, an industry that experienced no reductions in output or input tariffs would have a 15.7% lower labour share of value in 2007 than it actually did, assuming the same economy‐wide trends. Thus, our findings are consistent with the view that workers share part of the productivity gains from China's WTO accession identified by Brandt, Biesebroeck, Wang, and Zhang ().…”
Section: Introductionsupporting
confidence: 92%
“…Our estimates suggest that, on average, an industry that experienced no reductions in output or input tariffs would have a 15.7% lower labour share of value in 2007 than it actually did, assuming the same economy‐wide trends. Thus, our findings are consistent with the view that workers share part of the productivity gains from China's WTO accession identified by Brandt, Biesebroeck, Wang, and Zhang ().…”
Section: Introductionsupporting
confidence: 92%
“…These changes include reductions in export licensing requirements, production subsidies and import tari rates. Our controls draw on data from work on export licensing requirements by Bai et al (2015), on production subsidies from Khandelwal et al (2013), and on Chinese import tari rates from Brandt et al (2017). To account for the fact that reductions in barriers to foreign investment in China also declined at this time, we control for the share of industry inputs requiring relationship-specicity from Nunn (2007).…”
Section: Other Policy Variablesmentioning
confidence: 99%
“…With the development of measurement technology and data collection, the research of TFP has expanded from macro field to industry and enterprise level, which is also fit for China [6] . Brandt etc (2012) [7] had found that China's TFP had been improved based on empirical analysis. The growth of China's economy over the past 30 years has not just depended on capital input.…”
Section: Theoriesmentioning
confidence: 99%